Penguatan Fungsi Media Pada Gereja GBI Maranatha Salatiga Pada Masa Pandemi Oleh Mahasiswa PLT FISKOM - Yopi Yaser Umbu Lolu Yeda; Marcerio Britama Putra; Marthin Ronaldy Ledoh; Maria Kristian Dwi Rahayu; Anindy Pranavita; Triesanto Romulo Simanjuntak (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2021)
At the second year of the pandemic COVID-19 in Indonesia, worship activities at church are still doing in online method. Even though church have been opened, the capacity of church is still set at only 50% of the maximum capacity. So that online worship activities are become still a priority. Internship activities carried out by FISKOM’s students then came into contact with GBI Marantha Salatiga. FISKOM’s students maximized Internship activities for approximately 2 months to support worship activities during the pandemic. With the discussion method to find real needs, there were 4 main programs that would be carried out and aimed at strengthening the media function of the GBI Maranatha Salatiga. The four programs include: (1) making church video profile; (2) strengthening the church's multimedia team; (3) making a video about short info’s church ; (4) making new normal activity posters. These programs has been completed according to first designed and have been finished at a perfect time.